2020
DOI: 10.1177/8756087920978443
|View full text |Cite
|
Sign up to set email alerts
|

Controlling draw resonance during extrusion film casting of nanoclay filled linear low-density polyethylene: An experimental study and numerical linear stability analysis

Abstract: Commercially important extrusion film casting (EFC) processes for manufacturing plastic films or sheets are hampered by several instabilities that severely limits their productivity. In this research we focussed on one important instability: the draw resonance that occurs during the EFC process mainly under extensional flow conditions. Draw resonance is the sustained periodic oscillations in the film dimensions, notably film width and thickness, when the process operates beyond a critical draw ratio (CDR). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In our previous papers, 28,30,32 our research group has discussed in detail about how viscoelasticity manifested through slow, fast or averaged relaxation modes affect EFC stability. We showed that as the relaxation modes increased, there was a dramatic change in the stability regions.…”
Section: Controlling the Onset Of Draw Resonancementioning
confidence: 99%
See 3 more Smart Citations
“…In our previous papers, 28,30,32 our research group has discussed in detail about how viscoelasticity manifested through slow, fast or averaged relaxation modes affect EFC stability. We showed that as the relaxation modes increased, there was a dramatic change in the stability regions.…”
Section: Controlling the Onset Of Draw Resonancementioning
confidence: 99%
“…We showed that as the relaxation modes increased, there was a dramatic change in the stability regions. In the most recent paper, 32 we demonstrated that it was possible to reduce the draw resonance defect for a linear chain polyethylene such as LLDPE using 2.5 and 5 weight-percent well-dispersed nanclay (NC) fillers. Indeed, our numerical simulations as well as experimental data showed that enhanced melt elacticity for the nanoclay filled LLDPE formulations delayed the onset of draw resonance vis-à-vis the base unfilled LLDPE resin.…”
Section: Controlling the Onset Of Draw Resonancementioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8] Boehmite consists of aluminum oxide hydroxide nanoparticles. 9 Boehmite also has hydroxyl groups on the surface. Boehmite has important features such as transparency, mechanical strength, chemical resistance, and corrosion inhibition.…”
Section: Introductionmentioning
confidence: 99%